2015
DOI: 10.1021/acs.langmuir.5b01331
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Lipid Vesicles Spreading and Bilayer Formation on a Au(111) Surface

Abstract: Spreading of small unilamellar vesicles on solid surfaces is one of the most common ways to obtain supported lipid bilayers. Although the method has been used successfully for many years, the details of this process are still the subject of intense debate. Particularly controversial is the mechanism of bilayer formation on metallic surfaces like gold. In this work, we have employed scanning probe microscopy techniques to evaluate the details of lipid vesicles spreading and formation of the lipid bilayer on a A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“…These include scanning probe microscopy, infrared reflective absorption spectroscopy, quartz crystal microbalance, and for conductive supports, electrochemical methods can be used as well [8][9][10][11]. Most popular approaches for supported lipid membrane formation involve vesicles spreading or Langmuir-Blodgett and Langmuir-Schafer techniques [12][13][14][15]. It was demonstrated in numerous research papers that both can produce well-defined planar bilayers with good electrical insulating properties manifested by low differential capacitance and high membrane resistance [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…These include scanning probe microscopy, infrared reflective absorption spectroscopy, quartz crystal microbalance, and for conductive supports, electrochemical methods can be used as well [8][9][10][11]. Most popular approaches for supported lipid membrane formation involve vesicles spreading or Langmuir-Blodgett and Langmuir-Schafer techniques [12][13][14][15]. It was demonstrated in numerous research papers that both can produce well-defined planar bilayers with good electrical insulating properties manifested by low differential capacitance and high membrane resistance [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the amount of C16CA ligand on the water-redispersed AgNPs was twice that on the chloroform-redispersed AgNPs (see the Supporting Information). This indicates that a bilayer structure 58,59 was formed on the AgNPs surface. On the other hand, in the methanol solutions, the adsorption was lower and an almost flat isotherm was obtained.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…As a result, a lipid bilayer is formed by rupturing of the vesicles, unrolling, and spreading onto gold substrate. It is assumed that all of these steps depend on the vesicle size [12,13,15,16]. The VF process requires that the initial vesicle radius (R) is higher than the critical adsorption radius (Ra) and lower that the minimum rupture radius (Rr).…”
Section: Biomimetic Membranes On Electrodesmentioning
confidence: 99%
“…The lipid membrane becomes more fluid and stress within the membrane is released, which is closer to a real biological cell membrane [25]. Atomic force microscopy (AFM) [16], scanning tunneling microscope (STM) [16,26,27], and electrochemical scanning tunneling microscope EC-STM [28] techniques have been employed to obtain molecular imaging information and molecular level resolution about the electrode surface. sBLMs on gold electrodes behave as an ideal capacitor over a large potential range.…”
Section: Biomimetic Membranes On Electrodesmentioning
confidence: 99%
See 1 more Smart Citation